The Effectiveness of Education through Flashcard Media on Knowledge of Taking Medication in the Elderly with Hypertension at the Limboto Health Center, Gorontalo Regency - Sri Sulfanesa Pilominu; Zainuddin; Nur Ayun R. Yusuf (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypertension is a chronic disease that requires long-term treatment and medication to prevent complications. The success of therapy is influenced by the patient's understanding of the use of antihypertensive drugs. Good knowledge can support treatment, while lack of knowledge can lead to irregularities in treatment. One of the efforts to improve the knowledge of the elderly is through education using flashcard media. This study aims to determine the effectiveness of education through flashcard media on the knowledge of taking medication in the elderly with hypertension at the Limboto Health Center, Gorontalo Regency. This study uses a quantitative method with a pre-experimental one-group pretest-posttest design. The population was 71 people with a sample of 42 respondents selected using purposive sampling techniques. The research instruments were in the form of knowledge questionnaires and flashcard media. Data analysis used the Wilcoxon test. The results of the study showed that there was an effectiveness of education through flashcard media on the knowledge of taking medication in the elderly with hypertension with a p-value = 0.000 (? < 0.05). It was concluded that flashcard media is effective in increasing the knowledge of taking medication in the elderly with hypertension at the Limboto Health Center, Gorontalo Regency. This research is expected to contribute and become an input material for Puskesmas in the use of flashcard media as an educational medium to increase knowledge of taking drugs in the elderly with hypertension.